Breaking boundaries: a study of socio-cultural identities in archaic and classical western Sicily - Sommerschield, T (2019)
This thesis investigates the burial practices of western Sicilian settlements during the late Archaic and Classical periods, incorporating comparative epigraphic evidence. Specifically, it explores the processes of creation and assertion of socio-cultural identities among migrant and indigenous communities, rather than focusing solely on their pre-defined outcomes. The prioritisation of ethnicity in the definition of collective identities in this region and period continues to influence the ways the agents and dynamics of contact are conceptualised. Such ‘ethnic labelling’ is not only unwarranted in view of the available evidence, but also obfuscates our understanding of other types of identities and historical processes. To challenge these existing frameworks and heuristic models, this thesis analyses the burial evidence from Palermo, Monte Castellazzo di Poggioreale, Monte d'Oro di Montelepre, Himera and Solunto, and draws on comparative epigraphic evidence from the curse tablets and Meilichios horoi of Selinunte, and the tophet of Mozia. By examining the markers and features used by western Sicilian communities to assert and negotiate their social identities, this thesis reveals the complex ways in which social hierarchies, economic drivers, historical circumstances and regional intervisibility shaped funerary and epigraphic practices. This thesis argues that patterns (and discontinuities) in these practices were not imposed by pre-defined ethnic rationales, but were rather selected by local communities in response to their unique context of social mobility, polity interaction and regional connectivity.